Catalyst deactivation and regeneration for MTD reaction on Zr carbon-based catalyst - Torres-Liñán, Javier; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás; Rosas-Martínez, Juana María (Universidad de Alicante, 2019)
The aim of this work is the study of the deactivation and regeneration of a Zr-loading P-containing carbon catalyst on the dehydration of methanol to dimethyl ether. The Zr carbon-based catalyst showed a good performance in the methanol to DME reaction, with a high activity and selectivity to dimethyl ether (DME) at temperatures between 400-600ºC. Coke deposition reduces the activity and selectivity TO DME. Methane formation also increases with coke formation. Coke production takes place mainly on the narrow micropores at higher temperatures, firstly on Zr and then on P surface sites. Porosity parameters values remain the same after catalyst regeneration by oxidation treatment. Only a small fraction of coke is burnt due to the air treatment. The zirconium hydrogenphosphate specie seems to be the responsible of the long-term activity of the catalyst.
Keywords: Química; Dimathyl Ether; Carbon-based catalyst; Zr; Methanol